Literacy Teacher Educators Creating Space for Children's Literature - Lydia Menna; Clare Kosnik; Pooja Dharamshi (MDPI AG, 2020)
This paper reports on a qualitative research study that examined how 10 literacy teacher educators (LTEs) utilized children's literature to invite teacher trainees to critically engage with social issues, challenge their assumptions about literacy, and begin to develop the knowledge and dispositions to work alongside diverse learners (e.g., culturally, linguistically, socio-economically). The LTEs recognized that teacher trainees often entered their literacy courses with restricted conceptions of literacy and deficit assumptions about children from economically marginalized and/or culturally and linguistically diverse backgrounds. Within their courses, the LTEs positioned literacy as a multifaceted social practice, wherein access to a variety of representational resources facilitates the active construction of knowledge and identities. The LTEs modeled instructional strategies and designed assignments that encouraged teacher trainees to use children's literature as a means to connect with issues relevant to the lives of young learners within contemporary classrooms. This research will be of interest to LTEs who endeavor to use children's literature as a springboard to support teacher trainees to develop a self-reflective stance and a critical cultural consciousness.